What Factors Influence the Profitability of Firms in Malawi? Evidence from the Non-Financial Firms Listed on the Malawi Stock Exchange - Banda, Fredrick Mangwaya; Edriss, Abdi-Khalil (International Journal of Economics and Financial Issues, 2022)
For firms listed on the stock market, profit is crucial as it ensures the efficient allocation of scarce resources, and leads to the increase in the price of shares. The purpose of this study was to identify the drivers of profitability for the non-financial firms listed on the Malawi Stock Exchange (MSE). Previous studies have only focused on commercial banks without considering the determinants of profitability of non-financial firms. This study, therefore, adds to the literature by analyzing the drivers of profitability for non-financial firms listed on the MSE. It employs the panel data method, particularly, the Random Effects model (REM) using quantitative data collected from the financial statements of six non-financial firms listed on the MSE from the period 2014 to 2018. Regression results indicate that taxation and asset tangibility are the negative determinants of profitability on the MSE while non-tax debt shield (NDTS) and interest rate coverage ratio are positive determinants of profitability. The general policy implication arising from this study is that in order to make more profits managers of the firms should focus on increasing NDTS and interest coverage ratio, having more liquid assets than tangible ones, and reducing the corporate tax charged to firms.